The State, Urban Displacement and Land Rights in Nigeria - Nwobueze, Chibuzor Chile; Okolie-Osemene, James; Young, Ndu John (Advances in Social Sciences Research Journal, 2018)
The issues of urban displacement and land rights question have become the attributes of modern Nigerian state. The Fourth Republic is characterised by the arrogation of land by government. The nationalisation of land remains a watershed in land matters across Nigeria. This is based on how such development precipitated the phenomenon of cities in crisis with attendant urban vulnerabilities and creation of informal settlements. The recurrent urban displacement across the country has aroused a sense of how the phenomenon of contesting the city has received inadequate scholarly attention. In fact, various works have not established the intersection between state’s policies and urban crisis which raises a question of land rights in a nation that had customary land tenure prior to the 1978 Land Use Act. The demolition of so-called “illegal structures” has been a contentious issue owing to the fact that the process is usually characterised by controversies on whom or what determines an “illegal structure”, and “illegal inhabitants”. From Lagos to Owerri, Oyo, Ogun, Abia, Port Harcourt, to mention but a few extreme cases, where people living in the city and around waterfronts have been displaced; the issue of urban displacement remains prevalent. Using synthesised primary and secondary sources, this chapter is a case study of state’s leanings toward urban displacement. The government needs to review land laws and policies in order to promote urban cohesion, integration and cooperation from the various segments in the city especially the indigenous people rather than excluding and denying them access to the use of their land. The chapter suggests that there is need to prioritise welfare and adequate compensation of identified real occupants of the affected structures as well as resettling the people residing at informal settlements. This chapter concluded by asserting that, in order to prevent or mange conflicts and urban crisis, urban development or urban renewal projects should be carried out through a participatory approach and with appropriate resettlement programme for the occupiers or inhabitants of the proposed area or structure remarked for demolition or renewal.